A displacement based approach for seismic analysis and design of cantilever sheet pile walls under surcharge loading. (December 2021) - Singh, Akshay Pratap; Chatterjee, Kaustav
Abstract: An improved method is proposed for the design of cantilever sheet pile walls embedded in cohesionless soils and having an infinite uniform surcharge load under both static as well as seismic conditions in the framework of limit equilibrium. The proposed method considers the rigid rotation of cantilever sheet pile walls about a pivot point located near the toe of the wall following the displacement pattern. It considers the partial mobilization of earth pressures which is a function of lateral strain and depends on the magnitude and type of wall movements. Expressions are proposed to calculate the earth pressures on both sides of the wall in addition to shear force and bending moment at various depths. The penetration depth is obtained by considering horizontal force and moment equilibrium conditions simultaneously. The proposed method is compared with numerical, theoretical and experimental results under static as well as seismic conditions. It is found that the results proposed by this method and available literature are fairly good and reasonable. A parametric study is carried out to analyze the influence of friction angle of soil, magnitude and distance of surcharge under both static as well as seismic conditions.